1987
DOI: 10.1016/s0022-5347(17)44490-9
|View full text |Cite
|
Sign up to set email alerts
|

Drug-Induced Acute Interstitial Nephritis: Report of 10 Cases

Abstract: 10 patients with acute allergic interstitial nephritis were seen in a clinical nephrology service at a large regional hospital. The onset of renal failure was temporally related to the use of a drug: a nonsteroidal anti-inflammatory agent (NSAID) (in four patients), cimetidine (in three), antibiotics (in two) or allopurinol (in one). The onset of renal failure was acute in three patients and insidious in seven. Two patients also exhibited marked proteinuria. Clinical features such as fever, rash, hematuria, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0
1

Year Published

1992
1992
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 3 publications
0
13
0
1
Order By: Relevance
“…The evidence for the use of steroids to treat ATIN comes from small uncontrolled retrospective studies 5–9 with some reporting benefit and others showing no difference in outcome 10–13 . There is some evidence that steroids expedite initial recovery of renal function, although they may not influence longer‐term chronic kidney disease (CKD) 4 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The evidence for the use of steroids to treat ATIN comes from small uncontrolled retrospective studies 5–9 with some reporting benefit and others showing no difference in outcome 10–13 . There is some evidence that steroids expedite initial recovery of renal function, although they may not influence longer‐term chronic kidney disease (CKD) 4 .…”
mentioning
confidence: 99%
“…The evidence for the use of steroids to treat ATIN comes from small uncontrolled retrospective studies [5][6][7][8][9] with some reporting benefit and others showing no difference in Nephrology 17 (2012) 748-753 outcome. [10][11][12][13] There is some evidence that steroids expedite initial recovery of renal function, although they may not influence longer-term chronic kidney disease (CKD). 4 One recently published study has indicated the importance of early introduction of steroids to have an impact on renal outcome.…”
mentioning
confidence: 99%
“…These interactions with cimetidine are clinically significant because a decrease in drug clearance may lead to an increase in adverse effects, especially in the elderly and in those with impaired renal function. Numerous cases of acute interstitial nephritis have been reported with cimetidine therapy (Handa 1986;Kaye et al 1983;McGowan & Vermillion 1980;Richman et al 1981;Rudnick et al 1982). Renal biopsies of those cases all showed typical features of interstitial nephritis with infiltrates consisting of plasma cells, lymphocytes and eosinophils.…”
Section: Cimetidinementioning
confidence: 99%
“…A set of seven case series compared AIN treated with corticosteroids (52 patients) and without corticosteroids (48 patients) . Persistent renal dysfunction (S cr higher than 2.3 mg/dl) occurred in 17% of those treated with corticosteroids compared with 19% of those treated without corticosteroids (p value not reported).…”
Section: Discussionmentioning
confidence: 99%